Conceptual physical science - explorations / Paul G Hewitt, John Suchocki, Leslie A Hewitt - Hewitt, Paul G
An introduction to physics, chemistry, astronomy, and earth sciences. The authors use analogies and everyday examples to clarify key concepts and help students better understand the world around them. It combines active learning with critical thinking exercises, hands-on experiments, review questions, and quantitative problems.